Relationship between Religiosity and Anger Control with Marital Satisfaction - Maryam Bakhtiarvand; Hassan Nokarizi; Morteza Bakhtiarvand (Randwick International of Social Science Journal, 2023)
The purpose of this research is to investigate the relationship between religiosity and anger control with marital satisfaction. This research is the correlation type, which was carried out in the first term of academic year of 2012-2013. The instruments used were the Enrich Marital Satisfaction Questionnaire, the PACT Anger Control Questionnaire, and the Clark and Stark Religiosity Questionnaire, whose reliability was obtained according to Cronbach's alpha of 0.94, 0.81, and 0.92, respectively. The tests were carried out on 50 men and 50 married women of Shahid Chamran University of Ahvaz by random sampling, and finally 100 completed questionnaires were analyzed. Correlation research design and Pearson correlation method was used for data analysis in addition to descriptive statistics. The obtained results confirmed the research hypothesis and showed that there is a significant positive relationship between religiosity and anger control with marital satisfaction (p ≤ 0.000).